KENDALA PERIZINAN PENANAMAN MODAL ASING DI INDONESIA - Wibowo, Andika Wahyu; Rai Djaja, Ida Bagus (Kertha Negara : Journal Ilmu Hukum; Vol. 01, no. 01, Maret 2013, 2013)
To getting the good Indonesian economical, required the existence of investment activities, one of them is foreign investment. Implemation of Investment in Indonesia, unrarely have their own problems, such as related to licenses. The investor often to complaining about the unefficiency and lack of the facilities on the birocration licences management. The publication of Act No. twenty five of 2007 about the invesment does not necessarily provide ease in handling licencing and the other handling.
Keywords: Investment, Foreign Investment, Licences